Biochemical Study of Gallstones Compositions in Iraqipatients (Baghdad Science Journal, 2025)
The aim of this study is to determine the organic and inorganic components of bile and gallstones in Iraqi patients. Forty seven patients were included in this study with mean age (53+7) years and BMI (30.82+4.18) Kg/m2. Bile was classified according to its corresponding stones into: Bile of Mixed stones and Bile of pigment stones. IR spectra were studied for both types of stones and their bile in addition to biochemical analysis for organic and inorganic components. The organic components include: (cholesterol, bilirubin, bile salts, and phospholipids), while inorganic components include salts of: (calcium, phosphorus, iron, cupper and magnesium). The results reveal to there was significant low levels (p